2010
DOI: 10.1086/649871
|View full text |Cite
|
Sign up to set email alerts
|

Association of Human T Lymphotropic Virus 1 Amplification of Periodontitis Severity with Altered Cytokine Expression in Response to a Standard Periodontopathogen Infection

Abstract: HTLV-1 may play a critical role in the pathogenesis of periodontal disease through the deregulation of the local cytokine network, resulting in an exacerbated response against a standard periodontopathogen infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 44 publications
1
31
2
4
Order By: Relevance
“…IL-12 secretion by neutrophils was found to be elevated in asymptomatic and symptomatic HTLV-1 carriers[43]. IL-12 was also found to be elevated in HTLV-1 patients with periodontitis compared with patients with periodontitis only[44] and in HTLV-1 patients with HAM/TSP compared to uninfected patients with neurological diseases[45]. A type I interferon-induced gene signature has been identified in individuals with HAM/TSP but abnormal plasma levels of type I or type II IFNs haven’t been detected in those patients, probably because of the short half-lives of IFNs[46].…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 secretion by neutrophils was found to be elevated in asymptomatic and symptomatic HTLV-1 carriers[43]. IL-12 was also found to be elevated in HTLV-1 patients with periodontitis compared with patients with periodontitis only[44] and in HTLV-1 patients with HAM/TSP compared to uninfected patients with neurological diseases[45]. A type I interferon-induced gene signature has been identified in individuals with HAM/TSP but abnormal plasma levels of type I or type II IFNs haven’t been detected in those patients, probably because of the short half-lives of IFNs[46].…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms have been documented not only in HAM/TSP, but also in other diseases associated with HTLV-1 infection, including infective dermatitis,34 periodontal disease,27 HTLV-1-associated arthropathy,35 sicca syndrome,16 and isolated neurologic deficits 36. These findings clearly implicate HTLV-1 infection as central to the observed clinical pathology.…”
Section: Discussionmentioning
confidence: 79%
“…Over the last ten years, evidence has accumulated that, in addition to HAM/TSP and ATLL, HTLV-1 infection is capable of causing a variety of diseases including uveitis,9-11 periodontal disease,23, 27 sicca syndrome,16 HTLV-1 associated arthropathy,14, 15 and a large number of neurologic deficits 17-22. It is particularly striking that these findings occur in a large group of individuals traditionally considered to be asymptomatic HTLV-1 carriers, indicating that morbidity associated with HTLV-1 is much higher than has been previously considered 19, 28-31.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about IL-17 production in HTLV-1 infection. It has been reported that expression of IL-17 mRNA is induced by Tax in HTLV-1 infected T-cell lines [43] and increased in periodontal tissue of HTLV-1-infected subjects with periodontitis [71]. However, IL-17 production from a specific CD4 + T-cell subset is reduced among HAM/TSP patients [44].…”
Section: Resultsmentioning
confidence: 99%